Influence de la fatigue sur les paramètres biomécaniques de la foulée mesurés par accéléromètrie - Jidovtseff, B.; Rodriguez de la Cruz, C.; Bury, T.; Deflandre, D. (Science & Sports, 2019)
Aims of the study: The aim of the study was to investigate the influence of fatigue on stride biomechanics measured by a portable accelerometer, the MyotestRun. Opportunities of the protocol allowed additional analysis on the device reliability and sensitivity. Methods: Thirty-two male subjects, divided in two groups (runners and control), were involved in the study and achieved a treadmill progressive VO2max test; repeated run at constant velocity on a track and a field test at 90% of the VvO2max until exhaustion. The biomechanical measurements obtained from the MyotestRun allow exploring the reliability, the influence of speed, the differences between treadmill and track stride and the influence of fatigue. Results: Results show an excellent reproducibility of the MyotestRun values, except for the asymmetry of the stride. No significant stride difference appears between treadmill and track conditions. The progressive test shows that all the parameters evolve with speed increment, confirming the sensitivity of the MyotestRun. The study shows changes in the stride with the fatigue, such as an increase of the contact time, a decrease of the force. However any change in the stride frequency is observed. If the study shows that the fatigue pattern is more constant in the runners group it also highlights adaptations to fatigue that can be very different from one subject to another. Conclusion: This study confirmed that MyotestRun is a useful device in the stride analysis. The influence of fatigue on the stride is in accordance with most of the studies while confirming very important interindividual differences.